Anisotropic Bulk Viscous String Cosmological Model in a Scalar-Tensor Theory of Gravitation - D. R. K. Reddy; Ch. Purnachandra Rao; T. Vidyasagar; R. Bhuvana Vijaya (Advances in High Energy Physics)
Spatially homogeneous, anisotropic, and tilted Bianchi type-VI0 model is investigated in a new scalar-tensor theory of gravitation proposed by Saez and Ballester (1986) when the source for energy momentum tensor is a bulk viscous fluid containing one-dimensional cosmic strings. Exact solution of the highly nonlinear field equations is obtained using the following plausible physical conditions: (i) scalar expansion of the space-time which is proportional to the shear scalar, (ii) the barotropic equations of state for pressure and energy density, and (iii) a special law of variation for Hubble’s parameter proposed by Berman (1983). Some physical and kinematical properties of the model are also discussed.